Biomass-derived composite aerogels with novel structure for removal/recovery of uranium from simulated radioactive wastewater. (27th August 2019) - Chen, Tao; Zhang, Jian; Li, Mingxin; Ge, Huilin; Li, Yi; Duan, Tao; Zhu, Wenkun
Abstract: With the development of nuclear energy, the removal/recovery of radionuclides has attracted increasing attention. Here, an ultra-light, super-elastic, konjac glucomannan/graphene oxide composite aerogel (KGCA) as a high performance adsorbent for radionuclide removal/recovery was fabricated by a three-step process of freeze-casting, freeze-drying, and carbonization. The as-prepared bionic structured KGCA showed ultralow density, high specific surface area, desirable super-elasticity, and abundant oxygen-containing functional groups. Batch adsorption results demonstrated the maximum adsorption capacity of uranium (U(VI)) on KGCA is as high as 513.4 mg g −1, far exceeding other biomass carbon aerogels. Furthermore, KGCA showed good radiation stability, selective adsorption of U(VI), and high recycling performance. The KGCA also showed good adsorption properties even under simulated seawater or high salt concentration. Thus, these ultra-light and super-elastic biomass-derived composite aerogels could have a wide range of applications for nuclear wastewater treatment in the future.